Law Enforcement of Criminal Offense of Vehicle Registration Certificate Forgery: A Case Study of BPKB Forgery in the Bali Police Department - I Komang Prema Nanda Narendra Putra; Ni Ketut Wiratny (CV. Syntax Corporation Indonesia, 2024)
This research aims to explore how these differing definitions influence legal interpretations, law enforcement practices, and societal perceptions of crime. Additionally, the study will examine the impact of these definitions on the development of criminal law policies and how they affect the treatment of various offenses within the justice system. Thus, this research will provide a comprehensive analysis of the multifaceted nature of crime definitions and their implications for both theory and practice in the fields of law and criminology. Research method the type of research used in writing this thesis is a type of normative legal research which is supported by empirical research, namely by conducting research through observations in the field where the research is then compared with the concepts contained in the library materials used and statutory regulations. Invitation as a legal basis for solving problems. Conclusion Law enforcement of the criminal act of falsifying Motor Vehicle Owner's Books (BPKB) in the Bali Regional Police's legal area is as follows. Carrying out outreach to the public, spreading information that you should not easily believe the perpetrators of the criminal act of falsifying Motor Vehicle Owner's Books (BPKB). Report immediately if there is someone. Suspicious related to the criminal act of falsifying the Motor Vehicle Owner's Book (BPKB).